2023
DOI: 10.1021/acsomega.2c07044
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Solubility, Physicochemical Properties, and Cytotoxicity of Naproxen-Based Ionic Liquids

Abstract: To solve the problems associated with poorly water-soluble nonsteroidal anti-inflammatory drugs (NSAIDs), naproxen-based ionic liquids (ILs) containing naproxen as an active pharmaceutical ingredient (API) anion were prepared with benzalkonium (tetradecyldimethylbenzyl ammonium), choline, and 1-octyl-3-methylimidazole as the cation. The structures and thermal properties were analyzed. Through the conductivity method, the solubility at 25 and 37 °C and the critical micelle concentration (CMC) at 25 °C were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…[ 19,20,29 ] Recent studies have demonstrated that astaxanthin Z ‐isomers not only have higher bioavailability but also exhibit greater biological activities (e.g., antielastase, anti‐inflammatory, and antiaging activities) than the all‐ E ‐isomer. [ 8–10,30 ] Thus, boiling enhanced the nutritional value of L. vannamei .…”
Section: Resultsmentioning
confidence: 99%
“…[ 19,20,29 ] Recent studies have demonstrated that astaxanthin Z ‐isomers not only have higher bioavailability but also exhibit greater biological activities (e.g., antielastase, anti‐inflammatory, and antiaging activities) than the all‐ E ‐isomer. [ 8–10,30 ] Thus, boiling enhanced the nutritional value of L. vannamei .…”
Section: Resultsmentioning
confidence: 99%
“…The ILs characterized by this method include, for example, tetracycline docusate, 169 and cholinium, 1-octyl-3methylimidazolium, and benzalkonium naproxenates. 201…”
Section: Determination Of Relevant Solubility and Lipophilicitymentioning
confidence: 99%
“…These samples are subsequently centrifuged, and concentrations of the compounds are accessed in both phases by the same techniques described above. The ILs characterized by this method include, for example, tetracycline docusate, and cholinium, 1-octyl-3-methyl­imidazolium, and benzalkonium naproxenates …”
Section: Pharmaceutical Purity? Overview Of Current Synthesis and Cha...mentioning
confidence: 99%
See 2 more Smart Citations